Unmasking Higher-than-Expected Prevalence of Mycobacterium tuberculosis DNA in Respiratory Samples from US born Patients in a Safety Net Hospital in Boston. - Lopez, Edward Jones; Miller, Nancy; Orr, Berverley; White, Laura F.; Vinhas, Solange Alves; Mpeirwe, Moses; Orikiriza, Patrick; Mwanga, Juliet; Palaci, Moisés; Dietze, Reynaldo; Boum, Yap; Madico, Guillermo (My University, 2020)
The recent description of sequential inflammatory stages characterizing early tuberculosis (TB) disease and reports of disease caused by differentially culturable M. tuberculosis have significantly complicated the diagnostic landscape. These detection gaps threaten global TB elimination goals
Keywords: Mycobacterium; Tuberculosis; DNA; Respiratory Samples